Examination of the Relationship and Role of Situational and Product-Related Factors on Impulse Buying Behavior of Sports Product Consumers - Hasanpoor , Hosein; Tojari, Farshad; Nikaeen , Zinat (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study examined the situational factors and product-related factors influencing the impulse buying behavior of consumers of sports products. Methodology: The present study employed a survey method, with the research population consisting of customers of sports stores. Since this study utilized structural equation modeling (SEM), the principles for determining sample size in multivariate regression analysis were used to determine the sample size in SEM. A total of 598 participants were selected as the statistical sample through simple random and convenience sampling methods. The impulse buying behavior scale for sports consumers consisted of 19 items related to two main research variables and the impulse buying variable, comprising a total of three variables. Responses were rated on a five-point Likert scale continuum. All analyses were conducted at a 95% confidence level using SPSS and LISREL statistical packages. Findings: The findings of this study confirmed the causal relationship between situational factors and product-related factors with the impulse buying behavior of sports product customers. Conclusion: Overall, these results indicate that the intelligent combination of situational and product-related factors can help improve the shopping experience and increase sales in the sports product market. Companies can influence consumer decision-making by leveraging these factors, encouraging them to make immediate and impulsive purchases, ultimately leading to business growth and development.